'Not a Name Given by Mother': The Buddha's Epithet Bhagavat. - Visigalli, Paolo (Journal of Indian Philosophy, 2024)
This paper explores how Indic and Indic-derived linguistic analyses of the Buddha's epithet bhagavat influenced the epithet's interpretations and translations in the Sanskrit, Pali, Chinese, and Tibetan traditions. The paper consists of three parts. The first part examines and classifies the evidence into four types of analyses that ultimately reflect analytical models afforded by the Indic linguistic disciplines of grammar (vyākaraṇa) and etymology (nirvacana). The second part explores how these linguistic analyses coordinate with pronouncements emphasizing the epithet's extraordinary status as opposed to ordinary language terms. The third part examines how these analyses fostered the adoption of certain translations strategies in China and Tibet, focusing on the second of the 'Five Guidelines for Non-Translating' (wǔzhǒng bùfān 五種不翻) attributed to Xuanzang (600/602–664) and on pertinent statements recorded in the early-ninth-century Tibetan Sgra sbyor bam po gñis pa/Madhyavyutpatti. Using bhagavat as an example, this paper aims to demonstrate the important yet little-studied role that Indic and Indic-derived linguistic analyses had in South Asian Buddhism as well as in the Indianized Buddhist cultures of China and Tibet.